Optimalisasi Pendidikan Inklusi di Sekolah: Literature Review - Danny Ontario Rusmono (Universitas Kristen Satya Wacana, 2020)
The inclusive education that has been applied in Indonesia has many problems including the policy of the principal of the school, relation between teachers and their students, and also teachers often lack the ability to run the inclusive program. Teachers in this case are the crucial part of the school to run the program smoothly, because teachers do in fact communicate directly with the students in need and the other students. Knowledge, awareness, skills and experience of teachers determine how well inclusive program is run in a school, specifically in class. In order to achieve that, teachers need to undergo some trainings to help them prepare and execute the plan well. The search of e-literatures was conducted to identify journals published from 2015 to 2019 concerning steps necessary to optimize skills of teachers to achieve good unclusive environment. Electronic databases used were Proquest, Springer, Sage and Garuda. There were 7 studies used in this research after excluding studies that did not match to criteria used in this review. Optimizing inclusive program in school can be done by upgrading teachers’ skills through co-teaching training and traning of creating inclusive, learning-friendly environments. Aside from teachers, other school apparatus and parents should also given enough information regarding inclusive program and how to do it.